ANALISIS MODEL PENGEMBANGAN KURIKULUM BAHASA ARAB DI PERGURUAN TINGGI ISLAM - Nugraha, Rahmat Mulya; Ratna, Ai; Jamilah, Ayi Noer; Latopah, Leni; Sabila, Rabbaniah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Arabic curriculum development in Islamic universities plays an important role in improving students' competence in understanding and using the language which is the main source of Islamic teachings. This study analyzes the application of three curriculum development models: Tyler, Taba, and Schwab, as well as the advantages and challenges of each in the context of Arabic language education. The research method used is qualitative with a descriptive approach. Tyler's model offers a systematic approach based on learning objectives, while Taba emphasizes the active role of teachers in curriculum development inductively. Schwab's model focuses on the social, cultural and student needs aspects of educational practice. The results show that the Tyler Model has a systematic structure but lacks flexibility, the Taba Model is more adaptive but requires active involvement of the teacher, and the Schwab Model is more contextual but faces coordination challenges in its implementation. All three have the potential to complement each other when applied synergistically. The implications of the results of this study show the importance of the role of higher education institutions in adjusting the curriculum to the demands of the times as well as local and global needs. The combination of the three models is expected to produce an Arabic curriculum that is not only academically relevant, but also responsive to social and technological developments. This study recommends periodic curriculum evaluation and intensive training for teachers to improve the effectiveness of curriculum implementation on an ongoing basis. ABSTRAK Pengembangan kurikulum Bahasa Arab di perguruan tinggi Islam berperan penting dalam meningkatkan kompetensi mahasiswa dalam memahami dan menggunakan bahasa yang menjadi sumber utama ajaran Islam. Penelitian ini menganalisis penerapan tiga model pengembangan kurikulum: Tyler, Taba, dan Schwab, serta keunggulan dan tantangan masing-masing dalam konteks pendidikan Bahasa Arab. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Model Tyler menawarkan pendekatan sistematis berbasis tujuan pembelajaran, sementara Taba menekankan peran aktif pengajar dalam penyusunan kurikulum secara induktif. Model Schwab berfokus pada aspek sosial, budaya, dan kebutuhan mahasiswa dalam praktik pendidikan. Hasil penelitian menunjukkan bahwa Model Tyler memiliki struktur yang sistematis tetapi kurang fleksibel, Model Taba lebih adaptif namun menuntut keterlibatan aktif pengajar, dan Model Schwab lebih kontekstual tetapi menghadapi tantangan koordinasi dalam pelaksanaannya. Ketiganya memiliki potensi untuk saling melengkapi bila diterapkan secara sinergis. Implikasi dari hasil penelitian ini menunjukkan pentingnya peran lembaga pendidikan tinggi dalam menyesuaikan kurikulum dengan tuntutan zaman serta kebutuhan lokal dan global. Kombinasi dari ketiga model diharapkan dapat menghasilkan kurikulum Bahasa Arab yang tidak hanya relevan secara akademik, tetapi juga responsif terhadap perkembangan sosial dan teknologi. Penelitian ini merekomendasikan evaluasi kurikulum secara berkala dan pelatihan intensif bagi pengajar untuk meningkatkan efektivitas implementasi kurikulum secara berkelanjutan.